New indicators for measuring the manifold aspects of technical and economic efficiency of production processes and technologies - Barbiroli, Giancarlo (Technovation)
The measurement and evaluation of the technical and economic efficiency of a production process and, consequently, of the technologies adopted, are of great importance in establishing the advantage of carrying on the production activity as it has been programmed, or of modifying it. Since productivity analysis, although important, does not wholly represent the many quantitative aspects that affect the economic results that can be achieved with the combination of production factors, a complex method has been conceived and set up, based on indicators that make it possible, with a high degree of precision, to measure the manifold phenomena connected with production activities at both technical and economic levels. Such phenomena refer, at least, to : materials and energy cycle efficiency; process, product, energy cycle environmental efficiency; product absolute and constant quality efficiency; equipment static and dynamic operating efficiency; product mix variability, product volume and input efficiency. The indicators proposed can be elaborated either at the end of the year or periodically during the year, and have been arranged so that they are comparable with similar and different production activities, as can be seen from the three real cases reported. Global technical efficiency varies from 0 to 1200 and the higher the value the more favourable it is; global economic efficiency varies from 1200 to 0 and the lower the value the higher the efficiency.